Effect of Sales Promotion on Consumers Towards Fast-Moving Consumer Goods in Al-Dakhliyah Governorate. - Al Riyami, Moosa (Archives of Business Research, 2021)
The importance of consumer sales promotion in the marketing mix of the fast moving consumer goods (FMCG) category throughout the world has increased. Companies spend considerable time in planning such activities. However, there are few studies conducted in the Middle East to find out effectiveness of promotions. This aims to investigate consumer’s perceptions regarding sales promotion. Results indicate that there is a moderate correlation between consumers’ expectations and sales promotion in Al-Dakhliyah Governorate.